Enhanced cytostatic activity of the sesquiterpene lactone eupatoriopicrin by glutathione depletion. - Woerdenbag, H. J. (Nature Publishing Group, 1989)
Eupatoriopicrin (EUP), a sesquiterpene lactone from Eupatorium cannabinum L., possesses cytostatic activity. This was demonstrated for FIO 26 cells in vitro with the aid of a clonogenic assay and in vivo by tumour growth delay in FIO 26 and Lewis lung tumour-bearing mice. In vitro the IC50 for 1 h exposure to EUP was 1.5 microgram ml-1 (4.1 nmol ml-1). This concentration depleted about 25% of its cellular GSH concentration. Pretreatment of FIO 26 cells with BSO, resulting in greater than 99%. GSH depletion, enhanced the cytotoxic effect of EUP. The dose-enhancement factor at the level of 10% cell survival was 2.3. Growth inhibition of the Lewis lung carcinoma and the FIO 26 fibrosarcoma, solidly growing in C57Bl mice, was found after i.v. injection of 20 or 40 mg kg-1 EUP, at a tumour volume of about 500 microliters. Pretreatment with BSO at a dose of 4 mmol kg-1 i.p., 6 h before EUP administration, resulted in a significantly stronger growth delay of both tumours compared with EUP only. At the time of EUP treatment, cellular GSH in the tumours was reduced by BSO treatment to about 60%. It is concluded that EUP possesses antitumour activity in vivo and that chemosensitisation of EUP may be accomplished by pretreatment with BSO, indicating that endogenous GSH protects against the cytostatic action of EUP.